Using additive manufacturing technologies in high-field accelerator magnet coils. Issue 1 (1st May 2022) - Novitski, I; Coghill, J; Beale, T; Bergeron, J; Davidoff, R; Oshinowo, B; Raje, S; Swanson, D; Wilson, C; Zlobin, AV
Abstract: Recent advances with additive manufacturing (AM) technologies using various materials allow them to be considered for the manufacture of precise and complicated metal parts of the magnet coils of high field accelerator magnets from aluminum bronze, titanium alloy, stainless steel, etc. The 3D printing technology is also being used to fabricate prototype models of real parts to test and optimize their geometry. This paper discusses the designs of the complex stress-management coil parts developed at Fermilab, their fabrication using AM technologies, and quality control methods and results.